A Study on the Importance of the Construction of the Second Bridge Project in Kota Bharu, Kelantan - Ab Aziz, Mohamad Khairi; Othman, Muhammad Faris Izzat; Rosdi, Muhammad Shazrin Aiman; Hamid, Nor Baizura (Multidisciplinary Applied Research and Innovation, 2023)
Traffic congestion often occurs at the Sultan Yahya Petra Bridge, especially during peak hours or during the festive season, with a high number of vehicles entering Kelantan. This caused the government to propose the construction of the Palekbang-Penambang bridge project, which is the second bridge connecting Kota Bharu-Tumpat. The study was carried out at two different locations, namely the Sultan Yahya Petra Bridge and the construction site of the second bridge project. The purpose of this study was to determine the significance of the second bridge project based on feedback from respondents and road users about their satisfaction with the Sultan Yahya Petra Bridge. The respondents filled out a questionnaire on Google Forms, which was used to collect primary data. During the course of the study, 61 respondents were successfully collected. Quantitative methods, such as descriptive statistics in the form of percentages, were used to analyse the data collected from respondents. As a result, the analysis of primary and secondary data can provide a good resolution for identifying the factors that led to the construction of the second bridge project. The results show that the three categories that are critical to achieving the study's goals are satisfactory. The main factor in the construction of the second bridge, according to 90.2% of respondents, was traffic congestion. According to all respondents, bridge congestion is caused by a lack of infrastructure, such as new bridges or alternate routes to cross the Kelantan River. A more thorough investigation of the site or location of new bridge construction to meet basic needs should be revisited. To avoid traffic congestion, the parties involved must take this issue seriously by improving infrastructure or finding other alternatives to build a second bridge.